On transaction-cost models in continuous-time markets - Thomas Poufinas (International Journal of Financial Studies, 2015)
Transaction-cost models in continuous-time markets are considered. Given that investors decide to buy or sell at certain time instants, we study the existence of trading strategies that reach a certain final wealth level in continuous-time markets, under the assumption that transaction costs, built in certain recommended ways, have to be paid. Markets prove to behave in manners that resemble those of complete ones for a wide variety of transaction-cost types. The results are important, but not exclusively, for the pricing of options with transaction costs.
Keywords: C16; G11; G12; G13; G32; 330; risky asset; transaction costs; weakly complete markets; continuous-time markets; cost function; option pricing